Structure and Calibration of Constitutive Equations for Granular Soils - Sawicki, Andrzej; Sławińska, Justyna; Mierczyński, Jacek (Studia geotechnica et mechanica, 2015)
The form of incremental constitutive equations for granular soils is discussed for the triaxial configuration. The classical elasto-plastic approach and the semi-empirical model are discussed on the basis of constitutive relations determined directly from experimental data. First, the general structure of elasto-plastic constitutive equations is presented. Then, the structure of semiempirical constitutive equations is described, and a method of calibrating the model is presented. This calibration method is based on a single experiment, performed in the triaxial apparatus, which also involves a partial verification of the model, on an atypical stress path. The model is shown to give reasonable predictions. An important feature of the semi-empirical incremental model is the definition of loading and unloading, which is different from that assumed in elasto-plasticity. This definition distinguishes between spherical and deviatoric loading/unloading. The definition of deviatoric loading/unloading has been subject to some criticism. It was therefore discussed and clarified in this paper on the basis of the experiment presented.